Effect of soil aeration on root morphology and photosynthetic characteristics of potted tomato plants (Solanum lycopersicum) at different NaCl salinity levels - Li, Yuan (BMC Plant Biol, 2019)
BACKGROUND: Salt stress is one of the environmental factors that greatly limits crop production worldwide because high salt concentrations in the soil affect morphological responses and physiological and metabolic processes, including root morphology and photosynthetic characteristics. Soil aeration has been reported to accelerate the growth of plants and increase crop yield. The objective of this study was to examine the effects of 3 NaCl salinity levels (28, 74 and 120 mM) and 3 aeration volume levels (2.3, 4.6 and 7.0 L/pot) versus non-aeration and salinity treatments on the root morphology, photosynthetic characteristics and chlorophyll content of potted tomato plants. RESULTS: The results showed that both aeration volume and salinity level affected the root parameters, photosynthetic characteristics and chlorophyll content of potted tomato plants. The total length, surface area and volume of roots increased with the increase in aeration volume under each NaCl stress level. The effect was more marked in the fine roots (especially in ≤1 mm diameter roots). Under each NaCl stress level, the photosynthetic rate and chlorophyll content of tomato significantly increased in response to the aeration treatments. The net photosynthetic rate and chlorophyll a and t content increased by 39.6, 26.9, and 17.9%, respectively, at 7.0 L/pot aeration volume compared with no aeration in the 28 mM NaCl treatment. We also found that aeration could reduce the death rate of potted tomato plants under high salinity stress conditions (120 mM NaCl). CONCLUSIONS: The results suggest that the negative effect of NaCl stress can be offset by soil aeration. Soil aeration can promote root growth and increase the photosynthetic rate and chlorophyll content, thus promoting plant growth and reducing the plant death rate under NaCl stress conditions.